PRISMATIC SOCIETY THEORY STUDY OF THE SOCIAL FUNCTION OF LAND RIGHTS IN INDONESIA - Samun Ismaya (Kajian Hasil Penelitian Hukum, 2022)
Studies related to interests become an interesting study in the field of legal science, because law science itself makes interest as one of the objects of its study. Broadly speaking, interests are divided into two, namely personal interests and social interests. This interest can be attached to both moving objects and fixed objects (land).Attachment of interests to fixed objects, especially land, it is not uncommon for conflicts of interest to occur because humans (people) as legal subjects, on the one hand, are guaranteed their personal / civil interests, but on the one hand, humans cannot be separated from the social life of society. This concrete conflict of interest case occurs when national development requires land owned by community members to carry out public interests. There is a tug of war between private interests and public interests which often results in land conflicts that have broad socio-economic aspects.On the basis of the conflict of interest phenomenon, it becomes an interesting study from the perspective of legal science, especially legal theory, to be able to explain the meaning and implementation of the basic principle that "all rights to land have a social function" as stipulated in Article 6 of the UUPA. The meaning and implementation of self-interest which is social in nature is an interesting problem, especially in Indonesia, with the conditions of heterogeneous / plural socio-cultural values that can be studied inter-disciplinary and multi-perspective.To answer this problem, a descriptive analytical research was conducted using legal theory analysis tools, especially the theory that discusses the dualism of interests and the implementation of interests in social life (Theory Of Prismatic Social). As a source of research material, library research methods are used and the results of the research will be analyzed descriptively qualitatively with legal theory analysis tools and doctrines as an effort to answer the question of the meaning and implementation of personal and social interests inherent in a land right.The results of this research are expected to be useful for the development of science, especially law science and more specifically Land Law. In addition, this research is also expected to provide input in the efforts of making government policies related to land acquisition for development purposes